The Standards of the Inter-American Human Rights System regarding Migration and Its Impact on the Region’s States - (:unkn) unknown (Oxford University Press, 2024)
The protection and guarantee of the rights of migrants is one of the most important challenges currently facing the Inter-American Human Rights System (IAHRS). In addition to the complex dynamics of migration and the increase of restrictive migration pol...
Keywords: Migración; Derechos humanos